2023
DOI: 10.1002/agr.21833
|View full text |Cite
|
Sign up to set email alerts
|

Killing the sacred dairy cow? Consumer preferences for plant‐based milk alternatives

Peter Slade,
Mila Markevych

Abstract: We examine the relationship between demand for plant‐based milk alternatives and dairy milk using data from a survey and a discrete choice experiment completed by 902 Canadians. Our survey results show that most individuals who drink milk alternatives also consume dairy milk, and preferences for milk alternatives vary across consumption contexts. Using our experimental data, we estimate consumer preferences via a mixed logit model. These preferences are then used to calculate a set of price elasticities and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Our results confirm the conclusion that gender affects the actual buying behavior, as in the results of the studies in the literature. However, in the literature, the actual buying behavior of females is higher, which is different from our results [ 58 , 59 ]. When it is assumed that all these sociodemographic factors that increase actual buying behavior are collected in the same individual, it is thought that buying behavior may increase with multiple effects.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results confirm the conclusion that gender affects the actual buying behavior, as in the results of the studies in the literature. However, in the literature, the actual buying behavior of females is higher, which is different from our results [ 58 , 59 ]. When it is assumed that all these sociodemographic factors that increase actual buying behavior are collected in the same individual, it is thought that buying behavior may increase with multiple effects.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, price, brand, and whether there was a promotion or not affected the decision to purchase plant-based beverages ( Table 2 ). Studies in the literature have also shown that several factors including nutrient content, diet, socioeconomic status, health effects, environmental protection, and sustainability influenced the preference and purchasing behavior for plant-based beverages [ 10 , 17 , 57 , 58 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultra-processing serves multiple purposes, including enhancing the product's shelf life and imitating the taste, appearance, and texture of regular dairy-based milk [6]. Ethical and climate-conscious US consumers, as well as those following a vegan diet or those with dietary restrictions such as lactose intolerance or cow milk protein allergies, commonly favor plant-based milk alternatives [7][8][9][10]. Consumers with lactose intolerance often favor buying plant-based milk products over taking pills to help them digest lactose, as these medications can be rather expensive [11].…”
Section: Introductionmentioning
confidence: 99%
“…The rise in PBM popularity reportedly corresponds with a decrease in dairy milk sales [ 19 ]. Key drivers of this growth of PBM include the upgrading of taste, nutrient fortification, and increasing environmental and health awareness among consumers [ 20 , 21 , 22 ]. Public values related to environmental impact and animal welfare are notable influencers of demand for PBM [ 23 , 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%